2010
DOI: 10.1007/s13225-010-0026-4
|View full text |Cite
|
Sign up to set email alerts
|

The new genus Rostrohypoxylon and two new Annulohypoxylon species from Northern Thailand

Abstract: An inventory of xylariaceous pyrenomycetes of Northern Thailand resulted in the discovery of a new monotypic genus, here named Rostrohypoxylon as well as two new species of Annulohypoxylon. These new taxa are introduced, fully described and compared with similar species in this paper. The new genus is recognized based on new combinations of anamorphic and teleomorphic characters. The status of these new taxa is supported by secondary metabolite profiling using high performance liquid chromatography, coupled wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…These natural products, along with many other low molecular weight fungal metabolites, are classified as secondary metabolites (Keller et al 2005). Secondary metabolite production can be used in fungal systematics as demonstrated in chemotaxonomic studies carried out in Eurotiales and Xylariales (Guarro et al 1999) and Xylariaceae (Fournier et al 2010;Stadler 2011). New chromatographic techniques have resulted in a huge amount of secondary metabolite data which are now being incorporated into a database (Guarro et al 1999).…”
Section: Novel Metabolites and Toxins Produced By Cochliobolus Speciesmentioning
confidence: 99%
“…These natural products, along with many other low molecular weight fungal metabolites, are classified as secondary metabolites (Keller et al 2005). Secondary metabolite production can be used in fungal systematics as demonstrated in chemotaxonomic studies carried out in Eurotiales and Xylariales (Guarro et al 1999) and Xylariaceae (Fournier et al 2010;Stadler 2011). New chromatographic techniques have resulted in a huge amount of secondary metabolite data which are now being incorporated into a database (Guarro et al 1999).…”
Section: Novel Metabolites and Toxins Produced By Cochliobolus Speciesmentioning
confidence: 99%
“…Interestingly, the phylogeny inferred from ITS nrDNA data presented in the aforementioned studies revealed Daldinia to be split in two major clades, one being more closely related to Phylacia, Rhopalostroma and Thamnomyces , and another showing closer affinities with Entonaema and Ruwenzoria ( Stadler et al 2010b ), another recently recognised genus with aberrant morphological features that preclude its inclusion in Hypoxylon and Daldinia . The genus Rostrohypoxylon ( Fournier et al 2010a ) is another representative of the hypoxyloid Xylariaceae that could not be accommodated in the current generic concept, and seems to have evolved from within Annulohypoxylon , as judged from the outcome of a preliminary phylogenetic study ( Tang et al 2009 , where the type material was still treated as “ Xylariacae sp. JF 06-04”).…”
Section: Introductionmentioning
confidence: 99%
“…Within the Xylariaceae, the genera Annulohypoxylon and Hypoxylon have received recent attention. Annulohypoxylon and Hypoxylon occur around the world, and they are very well represented in Thailand [8], [10][12]. Taxonomic recognition of both genera and species relies on traditional morphological characters: shape, size, color, surface features and microscopic details of the asci and ascospores.…”
Section: Introductionmentioning
confidence: 99%
“…Taxonomic recognition of both genera and species relies on traditional morphological characters: shape, size, color, surface features and microscopic details of the asci and ascospores. Studies using scanning electron microscopy [13][15] and chemical and molecular data have sharpened the boundaries of both species and genera [10], [11], [15]–[20]. Nevertheless, the separation of some closely related species remains difficult, and as in other group of fungi the number of cryptic or sibling species can be high [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation